2006
DOI: 10.1002/jmri.20726
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative evaluation of the hepatic vascular anatomy in living liver donors: Comparison of CT angiography and MR angiography

Abstract: Purpose:To compare the diagnostic performance of CT angiography (CTA) and MR angiography (MRA) for preoperative hepatic vascular evaluation in living liver donors. Materials and Methods:Twenty-eight living donor candidates underwent preoperative CTA and MRA. Two blinded radiologists evaluated the anatomic types of the hepatic artery (HA) and portal vein (PV), and the number of aberrant hepatic veins (HVs) on both CTA and MRA, independently. Four grades of confidence levels were used to indicate the clarity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…Both of them can be used as noninvasive alternatives to catheter angiography before surgery. Accuracy of CTA and MRA for the depiction of hepatic arterial variants has been reported in several articles [10,15,16] , which suggested that three-dimensional CT or MR reconstruction should play an important part in the preoperative evaluation of complex hepato-biliary-pancreatic operations wherever possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of them can be used as noninvasive alternatives to catheter angiography before surgery. Accuracy of CTA and MRA for the depiction of hepatic arterial variants has been reported in several articles [10,15,16] , which suggested that three-dimensional CT or MR reconstruction should play an important part in the preoperative evaluation of complex hepato-biliary-pancreatic operations wherever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the accuracy in our series being 100%, the necessity of performing celiomesenteric angiography preoperatively for PD remains controversial because of its invasive nature. Recently, CT angiography (CTA) and magnetic resonance angiography (MRA) [10][11][12][13][14] have been used commonly to provide valuable preoperative information about abdominal vascular architecture. Both of them can be used as noninvasive alternatives to catheter angiography before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Preprocedural cross-sectional imaging of the liver and portal system can detect important contraindications to TIPS placement, such as multiple or huge hepatic cysts or hepatocellular carcinomas or obstruction or thrombosis of the portal or hepatic veins. 1,[9][10][11][12][13][14] Many researchers have investigated the relationships between diameter of the portal vein and portal pressure, 16 ‰ow direction, 17 development of the shunting vessels, 18 diameter of the shunting vessels and gastroesophageal bleeding, 19 or onset of encephalopathy. 20 Ito and associates 21 recently reported decreased diameter and hepatopetal ‰ow of the left gastric vein and the presence of non-variceal portosystemic shunt as predictive factors for variceal relapse after endoscopic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] We aimed to assess whether MR imaging evaluation of portosystemic collateral shunts can be used to predict therapeutic eŠectiveness of, complications after, and technical di‹culty during TIPS creation.…”
Section: Introductionmentioning
confidence: 99%
“…The detection and subsequent coil embolization of extra hepatic shunting to other gastro-intestinal structures is a major issue during SIRT simulation angiography [43,44]. According to Louie et al [45], the high spatial resolution of CBCT supplements the traditional use of DSA and 99mTc-MAA scintigraphy to predict extrahepatic microsphere deposition.…”
Section: Sirt Simulationmentioning
confidence: 99%